ANALISIS EFEKTIVITAS PROGRAM KARTU TANI DI KECAMATAN BANJARNEGARA KABUPATEN BANJARNEGARA - Mutiara Latifa Ashari; Dyah Hariani (Journal of Public Policy and Management Review, 2019)
Agricultural development is expected to be able to prosper the community by utilizing modern technology that is effective and sustainable. Agricultural activities are dominated by fertilizer use which aims to increase land production and commodity productivity. The reality that is often encountered by farmers is scarcity of fertilizer. Scarcity of fertilizer results in the difficulty of farmers in increasing land productivity. The government is working with Bank Rakyat Indonesia (BRI) to present a farmer card that aims to overcome various problems related to the availability of subsidized fertilizers while at the same time getting convenience in banking services. The form of the farm card is the BRI cobranding debit card, its use is done by swiping on the BRI EDC (Electronic Data Capture) machine that is placed at the retail stand. This study uses a descriptive method with a qualitative approach. The results of the program effectiveness research use four indicators, namely the success of the target, the achievement of overall goals, the availability of work facilities and infrastructure, and the system of supervision and control that is educational in nature. In the effectiveness of the farmer card program in Banjarnegara Subdistrict, Banjarnegara Regency there are driving factors and inhibiting factors that affect the program's effectiveness, namely technology, regional regulations, human resources, and the absence of a special budget for farmer cards. Suggestions given includes regular socialization, regeneration related to elderly human resources, procurement of budgets for farmer card programs, and increased coordination between complete retailer kiosks, farmers, and Banjarnegara District Agricultural Extension Center.